2011
DOI: 10.2298/hel1154089g
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the combining ability of dwarf restorer lines in sunflower (Helianthus annuus l.)

Abstract: The present investigation was undertaken to assess the combining ability for dwarfness among the given testers and also to estimate the extent of heterosis for ten different characters in 90 hybrids which were derived by crossing ten diverse cms lines with nine dwarf testers in a line × tester mating design during rabi 2008-09. The resultant hybrids and parents along with standard check RSFH-130 were evaluated for plant height and other yield contributing traits. CMS-107A among lines and R-411R among testers w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(5 reference statements)
1
1
0
Order By: Relevance
“…These variations show that the breeding material under investigation contains sufficient variance. Gejli et al (2011) and Khan et al (2019) also reported similar results for the traits studied in sunflower.…”
Section: Resultssupporting
confidence: 67%
“…These variations show that the breeding material under investigation contains sufficient variance. Gejli et al (2011) and Khan et al (2019) also reported similar results for the traits studied in sunflower.…”
Section: Resultssupporting
confidence: 67%
“…A wide range of variation was observed for all the characters for their mean performance among the parents. Several researchers studied the mean performance of parents in sunflowers (Gejli et al, 2011;Nasreen et al, 2014;Goksoy et al, 2020;Abdul-Hamed et al, 2021).…”
Section: Resultsmentioning
confidence: 99%